Moderniseringsprogrammet, 1983: resultatstyring version 1.0. - Gjørling, Mathias; Grøn, Caroline Howard (Politik, 2015)
The article explores the role of management by objectives in the modernization programme of 1983, which started the development of New Public Management in Denmark. e article is based on an interview with the civil servant who back in 1983 served as secretary for the committee who developed the programme, as well as previous versions of the programme made available to the authors. e article concludes that man- agement by objectives entered the programme almost incidentally and that the programme is much more focused on setting the public sector free with regards to inputs than controlling it with regard to outputs.